Kualitas Produk, Persepsi Risiko, Dan Kepercayaan: Faktor Yang Memengaruhi Keputusan Perempuan Berbelanja Online - Safitri Putri Derajat (Desanta Publisher, 2024)
This study aims to determine product quality, risk perception and trust in women's decisions to make online purchases at Shopee. This study consists of three independent variables, namely product quality, risk perception and trustworthiness and one dependent variable, namely purchasing decisions. The object of research is women who have made purchases at Shopee. The number of samples was determined as many as 60 people by purposive sampling technique. The research data was collected by distributing questionnaires. Data analysis used multiple linear regression method processed through the SPSS version 25 program. Based on the results of the study, it was found that 1) Product quality partially had a significant effect on women's decisions in making online purchases at Shopee; 2) Perception of risk does not partially affect women's decisions in making online purchases at Shopee; 3) Trust partially has a significant effect on women's decisions in making online purchases at Shopee; 4) Product quality, risk perception and trust simultaneously have a significant effect on women's decisions in making online purchases at Shopee. Trust is the variable that has the most dominant influence on purchasing decisions.